2000
DOI: 10.1172/jci8970
|View full text |Cite
|
Sign up to set email alerts
|

Glatiramer acetate (Copaxone®) induces degenerate, Th2-polarized immune responses in patients with multiple sclerosis

Abstract: Figure 4Cross-reactivity of GA-reactive T-cell lines is increased after daily injections of GA. Percentages of the GA-induced T-cell lines cross-reacting to each APL tested at each time point are shown for the 7 patients encoded by gray scale. Proliferative IFN-γ and IL-5 responses were examined for all T-cell lines and are represented separately in the top, middle, and lower third. A minimum SI of 2 and a difference of 2 SD over the background was required for classification as a cross-reactive T-cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
231
1
11

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 407 publications
(268 citation statements)
references
References 38 publications
25
231
1
11
Order By: Relevance
“…Our own studies suggest that when chronically administered to patients with MS, GA is capable of inducing immune deviation, which may result in amelioration of inflammatory responses (23). The apparent universal immunogenicity of GA suggests the possibility that GA could serve as the ultimate helper epitope.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our own studies suggest that when chronically administered to patients with MS, GA is capable of inducing immune deviation, which may result in amelioration of inflammatory responses (23). The apparent universal immunogenicity of GA suggests the possibility that GA could serve as the ultimate helper epitope.…”
Section: Discussionmentioning
confidence: 85%
“…Our preliminary findings in an earlier study supported this hypothesis. We found that the GA-mediated proliferation of GA-reactive T cell lines was inhibited by the monoclonal anti-DR Ab LB3.1 but not by the monoclonal anti-DQ Ab IVD12 (23). Both LB3.1 and IVD12 have previously been shown to recognize nonpolymorphic determinants present on DR and DQ molecules, respectively, and to inhibit the proliferation of DR-and DQ-restricted T cell responses.…”
Section: Ga-reactive T Cell Lines Are Hla Dr Restrictedmentioning
confidence: 75%
See 1 more Smart Citation
“…In der antiinflammatorische Zytokine (Duda et al 2000). Ob GA über eine Induktion der PHB- (Nijtmans et al 2000).…”
Section: Diskussionunclassified
“…Por outro lado, a ação terapêutica do acetato de glatirâmer é principalmente devida à expansão de células Th2-específicas com propriedades imunoreguladoras 28 . …”
Section: Classificação Das Formas Evolutivas Da Esclerose Múltiplaunclassified